Road narratives and hinterland in Brazilian contemporary literature and cinema - Santini, Juliana [UNESP] (Associacao Internacional de Lusitanistas, 2019)
This work presents an analysis of Viajo porque preciso, volto porque te amo, a motion picture by Marcelo Gomes e Karim Aïnouz, and Milagre em Juazeiro, a short story by Ronaldo Correia de Brito. The proposed question is how the characteristics of road narratives are related, in both cases, to a revision of the meanings assumed by hinterland during different periods in Brazilian literature and cinema.
Narrativas de estrada e o sertão na literatura e no cinema brasileiros contemporâneos
Keywords: displacement; hinterland; road narratives